The Role of Different Emotional States of Customers on Food Preferences - Mahmood Ghanbari; Kambiz Heidarzadeh Hanzaee; Behnaz Khodayari; Maryam Khalili Araghi (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe purpose of this research is the role of different emotional states of customers on the preference of choosing (type) of food. The current research is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of execution. The statistical population of the research in the qualitative part includes 26 people from the food consumers of restaurants and food courts in shopping centers of Tehran (Arg, Kurosh, Palladium, Sana, Iran Mall, etc.), and sampling was done in the targeted manner; and the quantitative part includes 448 persons who, like the qualitative part, were selected randomly available from the consumers of food. The research collection tool is a semi-structured interview and a questionnaire taken from the qualitative section. Data-based theory and MAXQDA software were used for data analysis, and multivariate analysis and structural equations were used in the quantity part. The results showed that there are two components in the experienced excitement: positive emotion, and negative emotion; and for background factors, three components of culture, health knowledge, and previous experience; and five components for food selection conditions in positive emotional conditions; and five components for negative emotional conditions have been identified. The results have shown that people go to different foods in different experienced emotions (positive and negative), and different characteristics of food (texture, color, temperature, aroma, taste) played an important role in their choice in both positive and negative emotions. On the other hand, background factors also affect the conditions of food selection and people have chosen food based on texture, color, temperature, aroma and taste in negative or positive emotional conditions.Extended Abstract                                           IntroductionOne of the important features of emotions for both researchers and providers of goods and services is that they are said to be triggered by events that occur in the environment and depend on social and interpersonal dynamics (Tombs & Tuzovic, 2013). Food preference is the study of those factors that influence choice. Taste preferences that influence food choices vary among individuals depending on many factors such as culture, learning experiences, and genetics. The first level of information that determines whether to consume or avoid a food is conveyed through sensory stimuli. Sight, smell, and taste, as well as the perception of temperature or texture, provide this basic information. Next, post-digestive effects such as satiety and memory affect appetite and taste preferences (Bouchard & Ordovas, 2012). Regarding the amount of food eaten, previous studies have shown that people consume more food when experiencing positive and negative emotions compared to when they are not experiencing any emotional fluctuations. Specifically, obese individuals often show greater food intake when experiencing negative emotions. Some researchers have found that negative emotions lead to overeating, while others have reported the opposite trend. As a result, the amount of food received is more or less influenced by negative emotions. The effect of emotions on the type of food eaten has also been documented (Chao et al, 2015). Therefore, the main question of the research is: What is the role of different emotional states of customers on the preference of choosing (type) of food?Theoretical FrameworkThe excitement of foodDifferent types of emotions, such as negative and positive emotions in previous researches, along with emotions triggered by certain food items, as well as previously experienced emotions that create specific results in consumers, such as customer satisfaction and product choice, have been investigated. Accordingly, eating is thought to be a response mechanism, particularly to negative and positive emotions. Excessive and unhealthy food consumption behavior is one of the main drivers for the growing epidemic of obesity and overweight worldwide, which makes it a serious health threat worldwide (WHO, 2020).The importance of excitement in choosing foodAs a reaction to the cognitive evaluation of environmental stimuli, emotion is an integral part of human behavior and performance (Adolphs et al, 2019). Emotions affect human behavior in different ways and can affect food consumption and food-eating decisions regarding the amount and time of certain foods (Ha & Lim, 2023).The role of positive emotion in food choice Although research often highlights the link between negative emotions and eating, positive emotions have also been found to influence food consumption. For example, Evers et al, (2013) suggest that positive emotions play an important role in food consumption as much as negative emotions. Using a study, they found that specifically in everyday life, more snacking appeared when experiencing positive emotions, leading to higher caloric intake as a response to positive emotional arousal.The role of negative emotion in food choiceNegative emotions have an effect on food choices. People turn to different foods when dealing with different emotions. Increased food consumption in emotional and psychological conditions such as stress may have a negative effect on health. An unbalanced diet may promote many chronic diseases such as obesity, diabetes, high cholesterol, high blood pressure, heart disease, and stroke (Konttinen, 2020).Ogundijo et al, (2022) investigated factors affecting food choices and consumer purchasing habits in an English university setting. They showed that the choice of food has a lot of complexity. Food selection factors vary depending on life stage, and the strength of a factor varies from one individual or group of individuals to another. In this case, background factors affect the decision of choosing food. Depending on changes in lifestyle, food choices are becoming more complex, and consumers are faced with making informed decisions based on more diverse factors. Among the background factors influencing the choice of food based on the findings of this research in different emotions are culture, previous experience of food consumption, and health knowledge of food consumption.Crina Petrescu et al, (2020) showed in their study that customers mostly use freshness, taste and appearance of food to evaluate food quality. These researchers showed that the health of food also includes ingredients, information on nutrients and information related to additives, and environmental effects in terms of packaging, authenticity of food, and production method.Research methodologyThe current research is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of execution. The statistical population of the research in the qualitative part includes 26 people from the food consumers of restaurants and food courts in shopping centers of Tehran (Arg, Kurosh, Palladium, Sana, Iran Mall, etc.), and sampling was done in the targeted manner; and the quantitative part includes 448 persons who, like the qualitative part, were selected randomly available from the consumers of food. The research collection tool is a semi-structured interview and a questionnaire taken from the qualitative sectionResearch findingsData-based theory and MAXQDA software were used for data analysis, and multivariate analysis and structural equations were used in the quantity part. The results showed that there are two components in the experienced excitement: positive emotion, and negative emotion; and for background factors, three components of culture, health knowledge, and previous experience; and five components for food selection conditions in positive emotional conditions; and five components for negative emotional conditions have been identified. The results have shown that people go to different foods in different experienced emotions (positive and negative), and different characteristics of food (texture, color, temperature, aroma, taste) played an important role in their choice in both positive and negative emotions. On the other hand, background factors also affect the conditions of food selection and people have chosen food based on texture, color, temperature, aroma and taste in negative or positive emotional conditions.ConclusionThe current research was conducted with the aim of the role of different emotional states of customers on the preference of choosing (type) of food. The results of this research are in agreement with the results of Ebrahimi et al, (2023), Ogundijo et al, (2022), Olegario et al, (2021), Mohammadi et al, (2022), Ebrahimi et al, (2021), Crina Petrescu et al, (2020), Lefebvrea et al, (2019), Mantau et al, (2018), and Frayn et al, (2018). Ogundijo et al, (2022) showed that food selection is highly complex. Food selection factors vary depending on life stage, and the strength of a factor varies from one individual or group of individuals to another. In this case, background factors affect the decision of choosing food. Depending on changes in lifestyle, food choices are becoming more complex, and consumers are faced with making informed decisions based on more diverse factors. The background factors influencing the choice of food based on the findings of this research in different emotions include culture, previous experience of food consumption, and knowledge of food consumption health.According to the present research, the following suggestions are presented:It is necessary for restaurants and food courts to include a variety of foods that can respond to different emotions (negative and positive) of people in their daily menus for breakfast, lunch and dinner, because sometimes people go to the same foods in negative and positive emotional conditions.